PENGAJARAN HOLISTIK PENDEKATAN TVET INSTITUSI PENJARA - Muhamad Afzamiman Aripin, author 491260; Kamisah Kamin, author 650680; Zainah Pardi, author 650681 (Johor Bahru, Johor : PENERBIT UTM PRESS, 2023)
Includes bibliographical references and index.